Diabetes Mellitus and Its Neurological Sequelae: A Narrative Review - Naveed, Muhammad (Biological and Clinical Sciences Research Journal, 2025)
Diabetic polyneuropathy (DPN) is among the most common chronic complications of diabetes mellitus (DM), affecting approximately 50% of individuals with the disease. Characterized by progressive damage to peripheral nerves—especially in the lower extremities—DPN leads to significant impairments in motor, sensory, and autonomic function. It is particularly prevalent in industrialized regions and is associated with substantial morbidity, diminished quality of life, and increased socioeconomic burden. Objective: This review aims to synthesize current evidence on the epidemiological patterns, diagnostic complexities, and socioeconomic impacts of diabetic polyneuropathy, with an emphasis on guiding improved clinical and public health strategies. Methods: A comprehensive literature review was performed using electronic databases including PubMed and EMBASE. Studies published in peer-reviewed journals from the past decade were selected based on relevance to DPN epidemiology, diagnostic modalities, and socioeconomic implications. Keywords employed in the search included “diabetes mellitus,” “diabetic neuropathy,” “polyneuropathy,” and “diabetic neuropathic pain (DNP).” Both original research articles and systematic reviews were included in the analysis. Results: DPN is reported in up to 50% of individuals with diabetes, with higher prevalence observed in populations aged over 50 years. Clinical manifestations commonly include burning pain, tingling, numbness, and sleep disturbances. Delayed diagnosis remains a major challenge, often resulting in irreversible complications such as foot ulcers and amputations. Pharmacologic management—comprising serotonin-norepinephrine reuptake inhibitors, sodium channel blockers, and certain antidepressants—provides symptomatic relief but lacks disease-modifying efficacy. Evidence supports that early identification and comprehensive management strategies can mitigate disease progression and improve patient-reported outcomes. Conclusion: Diabetic polyneuropathy constitutes a major public health concern due to its high prevalence, diagnostic challenges, and adverse impact on quality of life and healthcare resources. Enhancing early detection and implementing multidisciplinary management protocols are essential to reducing the individual and systemic burden of the disease.